PENGARUH KOMPLEKSITAS BISNIS KLIEN, SPESIALISASI AUDITOR, DAN UKURAN KOMITE AUDIT TERHADAP AUDIT REPORT LAG - Rizky Maulana (2022)
This study is a quantitative study that aims to examine the effect of audit complexcity, auditor specialization, and audit committee size on Audit Report Lag. This study uses audited financial report data for energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The selection of sample criteria was carried out using a purposive sampling technique with predetermined criteria and 75 data samples were obtained from 37 energy sector companies. Hypothesis testing in this study used panel data regression equation analysis with the STATA 16 program with a significance level of 5% (0.05). The results of this study indicate that 1) the complexity of the client's business has no effect on Audit Report Lag; 2) auditor specialization has no effect on Audit Report Lag; 3) the size of the audit committee has no effect on the Audit Report Lag; 4) the Covid-19 pandemic has a positive and significant impact on the Audit Report Lag.